Determination of βS haplotypes in patients with sickle-cell anemia in the state of Rio Grande do Norte, Brazil - Cabral,Cynthia Hatsue Kitayama (2011)
βS haplotypes were studied in 47 non-related patients with sickle-cell anemia from the state of Rio Grande do Norte, Brazil. Molecular analysis was conducted by PCR/RFLP using restriction endonucleases XmnI, HindIII, HincII and HinfI to analyze six polymorphic sites from the beta cluster. Twenty-seven patients (57.5%) were identified with genotype CAR/CAR, 9 (19.1%) CAR/BEN, 6 (12.8%) CAR/CAM, 1 (2.1%) BEN/BEN, 2 (4.3%) CAR/Atp, 1 (2.1%) BEN/Atp and 1 (2.1%) with genotype Atp/Atp. The greater frequency of Cameroon haplotypes compared to other Brazilian states suggests the existence of a peculiarity of African origin in the state of Rio Grande do Norte.